Ethical decision-making under empirical and moral uncertainty - Theisen, Maximilian; Germar, Markus; Funke, Joachim (Open Science Framework, 2020)
This study compares the role of empirical and moral uncertainty in ethical decision-making. Empirical uncertainty refers to uncertainty about non-normative empirical states, such as the outcome of an action. Moral uncertainty refers to uncertainty about moral principles, such as whether a deontological or consequentialist reasoning should be applied in a given situation. Following the meta-ethical literature on moral uncertainty, we propose that decisions under moral uncertainty can be described by applying a form of expected-value reasoning. According to this approach, the product of both the credence a person has in a moral position and the moral value this moral position would ascribe to the given action, summed over all moral positions, predicts the moral judgment of the respective action. - We are running an online study with 200 undergraduate students to compare the influence of empirical uncertainty on a purely consequentialist evaluation to the influence of moral uncertainty on a personal evaluation that might include both consequentialist and deontological reasons.
Gesehen am 26.02.2026